Impact of tumor, treatment, and access on outcomes in bladder cancer: Can equal access overcome race‐based differences in survival?. Issue 8 (11th January 2019) - Cole, Alexander P.; Fletcher, Sean A.; Berg, Sebastian; Nabi, Junaid; Mahal, Brandon A.; Sonpavde, Guru P.; Nguyen, Paul L.; Lipsitz, Stuart R.; Sun, Maxine; Choueiri, Toni K.; Preston, Mark A.; Kibel, Adam S.; et al.
Abstract: Background: There are race‐based differences in bladder cancer survival. To better understand this phenomenon, this study was designed to assess the statistical contributions of tumor, treatment, and access variables to race‐based differences in survival. Methods: Data were extracted from the National Cancer Data Base on black and white adults with muscle‐invasive bladder cancer from 2004 to 2015. The impact of tumor, access, and treatment variables on differences in survival was inferred by the performance of sequential propensity score–weighted analyses in which black and white patients were balanced with respect to demographics and health status (comorbidities) tumor characteristics, treatment, and access‐related variables. The propensity score–weighted hazard of death (black vs white) was calculated after each iteration. Results: This study identified 44, 577 patients with a median follow‐up of 77 months. After demographics and health status were balanced, black race was associated with 18% worse mortality (hazard ratio, 1.18; 95% confidence interval [CI], 1.12‐1.25; P < .001). Balancing by tumor characteristics reduced this to 16%, balancing by treatment reduced this to 10%, and balancing by access‐related variables resulted in no difference. Access‐related variables explained 40% (95% CI, 22.9%‐57.0%) of the excess risk of death in blacks, whereas treatment factors explained 35% (95% CI, 22.2%‐46.9%). The contribution of tumor characteristics was not significant. Conclusions: In the models, differences in survival for black and white patients with bladder cancer are best explained by disparities in access and treatment, not tumor characteristics. Access to care is likely a key factor in racial disparities in cancer. Abstract : This study analyzes the determinants of racial disparities in bladder cancer. The results suggest that access to care, not differences in treatment or tumor biology, explains much of the disparity in outcomes for bladder cancer.